Diminishing partnership: bankers strategic response to Shariah compliance home financing - Abdul Razak, Dzuljastri; Ismail, Yusof (2010)

(untitled)
Diminishing Partnership (DP) is a relatively new concept in home financing which is based on equity compared to the established debt concept used in conventional and BBA home financing. Under DP home financing, customer and bank share profit based on the rental value of the house instead of predetermined interest rate where bank gains profit upfront .As such DP is claimed to be fairer and more flexible than debt financing which result in more justice, equality and cater for societal well being that is in line with the Maqasid al Shariah. This research adopted a mixed method by obtaining the perceptions of three stakeholders namely consumers, Shariah scholars and bankers. Four common issues were investigated namely, concept used, method of computing and pricing, Shariah compliance and preference for the product. The main findings indicated that consumers perceived that DP home financing fulfills their needs better than the debt financing concept. The Shariah scholars also agreed that DP possesses justice, fairness and cater for the well being of individual and society. Contrary to expectation, the overall views of the bankers support the implementation of DP except for a few reservations regarding pricing and operations.